Age-related rates of decline in performance among elite senior athletes - Wright, V. J.; Perricelli, B. C. (The American Journal of Sports Medicine, 2008)
Age-related disability and lost independence currently plague one third of older Americans. Many causes of disability, lost muscle mass and bone mineral density, are modifiable with exercise. Most exemplary of successful aging are the Senior Olympians; this group of vital athletes exhibit persistently high levels of functional capacity.